Super-resolution and optical sectioning integrated structured illumination microscopy. (2nd December 2020) - Dan, Dan; Gao, Peng; Zhao, Tianyu; Dang, Shipei; Qian, Jia; Lei, Ming; Min, Junwei; Yu, Xianghua; Yao, Baoli
Abstract: Super-resolution structured illumination microscopy (SR-SIM) has attracted a great deal of attention in the past few decades. As a wide-field imaging technique, SR-SIM usually suffers from issues relating to out-of-focus background, particularly when imaging thick samples. In this study, we develop an integrated SIM with simultaneous SR and optical sectioning (OS) capabilities, facilitating SR imaging of stacked optical sections, with the out-of-focus background suppressed. The combination of the merits of SR and OS is realized by means of a new image reconstruction algorithm. We confirm the validity of the integrated SIM, both experimentally and in simulation. We anticipate that this integrated SIM will assist biologists in obtaining much clearer SR images in relation to thick specimens.